Pengaruh Media Gambar terhadap Hasil Belajar Siswa pada Tema 1 Subtema 3 di Kelas V SD Negeri 091400 Dolok Saribu - Lailany N.I Girsang; Lisbet N. Sihombing; Eva Pasaribu (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This study aims to determine: The Effect of Picture Media on Student Learning Outcomes in Theme 1 Sub-theme 3 "The Environment and Its Benefits" in Class V SD Negeri 091400 Dolok Saribu T.A 2022/2023. This research is a quantitative study using experimental methods. The population of this study were all students of class VA and VB SD Negeri 091400 Dolok Saribu T.A 2022/2023 as many as 40 students. While the sample in this study were 40 students. The instruments used are pretest and posttest in the form of multiple choice questions that have been tested for validation and reliability. The results of the study at the 0.05 level showed that: There was an effect of using Picture Media on the learning outcomes of fifth grade students at SD Negeri 091400 Dolok Saribu. Based on the data analysis, the pretest and posttest values ??show that the value of sig (2-tailed) is 0.00 0.05, where Ho is rejected and Ha is accepted so that it can be concluded that there is a significant effect between increasing student learning outcomes using image media and increasing student learning outcomes. learning outcomes of students who do not use image media.